Effect of temperature and hydraulic retention time on hydrogen production from palm oil mill effluent (POME) in an integrated up-flow anaerobic sludge fixed-film (UASFF) bioreactor - Zainal B.S.; Gunasegaran K.; Tan G.Y.A.; Danaee M.; Mohd N.S.; Ibrahim S.; Chyuan O.H.; Nghiem L.D.; Mahlia T.M.I. (Elsevier B.V., 2023)
Anaerobic digestion; Bioconversion; Efficiency; Effluents; Hydrogen production; Palm oil; Temperature; Wastewater treatment; Anaerobic sludge; Bio-hydrogen; COD removal efficiency; Fixed film; Hydraulic retention; Hydraulic retention time; Integrated bioreactors; Palm oil mill effluent; Palm oil mill effluents; Retention time; Bioreactors